The impact of performing arts festivals on tourism development: Analysis of participants' motivation, quality, satisfaction and loyalty - Amorim, Daniela (2020)
The festivals have had a very positive impact on tourism development, and on the promotion of destinations, they are positioned as important attractive elements that boost tourism in the several regions, as well as its economic and cultural development. This study aimed to analyse the motivation, quality, satisfaction and loyalty of two performing arts festivals participants (Andanças, Portugal and La Sierra, Spain). It followed a quantitative methodology, and questionnaires were applied to the participants of the events under analysis. The results of the test-t indicate that La Sierra festival participants (n=235), compared to Andanças festival participants (n=297), perceive the festival as having more quality (catering, hotel, information and transport), and are more faithful to the festival (even if prices increase). The results obtained contribute to a better understanding of the needs and perceptions of participants who practice festival tourism, particularly in performing arts festivals, supporting the manager's strategies in organising this type of event.